Student needs assessment analysis in e-commerce courses of vocational colleges in Guizhou Province China - Tan, Linxi; Ratanaolarn, Thanin; Sriwisathiyakun, Kanyarat; Cui, Jianming (Edelweiss Applied Science and Technology, 2025)
This study aimed to identify the specific needs of students in e-commerce courses in vocational colleges, focusing on digital marketing competencies, team spirit, learning methods, and course content to support curriculum development and the construction of innovative teaching models. The researcher of this study conducted a needs assessment survey with a sample size of 400 current vocational students. The collected data were analyzed using descriptive statistics to determine the means of 12 items. The results showed that the mean value of items ranged from 3.44 to 4.29, and all items reached at least the need level. Furthermore, respondents perceived a strong need to enhance digital marketing competencies and adopt new learning methods in e-commerce courses. Respondents also showed a need to integrate project-based learning and blended learning compared to other learning methods. A comprehensive student needs assessment analysis towards e-commerce courses has been provided in this study; it could serve as basic information for educators to develop a better teaching model and curriculum in the field of e-commerce education in vocational colleges.